2016
DOI: 10.1007/s11356-016-7643-8
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in surface sediments of the shallow lakes in eastern China: their relations with environmental factors and anthropogenic activities

Abstract: The aquatic environment is affected by heavy metal pollution. This study was conducted to test the hypothesis that environmental factors and anthropogenic activities influence the distributions and the risks posed by heavy metals in surface sediments in shallow lakes in eastern China, which is an area affected by rapid urbanization, industrialization, and population growth. Total Cd, Cr, Cu, Ni, Pb, Se, and Zn concentrations in sediment samples were determined using inductively coupled plasma optical emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 39 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…Compared with previous studies [3,4], the concentrations of Tl and Co in Poyang Lake were found to have increased slightly ( Table 2), suggesting that they were influenced by anthropogenic activities in the Poyang Lake basin. This is consistent with previous studies showing how anthropogenic activities [31], such as hydro-engineering works [44], shipping, mining, and agriculture, affect metal concentrations in Poyang Lake.…”
Section: Concentrations and Spatial Variability Of Tl And Co In The Ssupporting
confidence: 93%
See 2 more Smart Citations
“…Compared with previous studies [3,4], the concentrations of Tl and Co in Poyang Lake were found to have increased slightly ( Table 2), suggesting that they were influenced by anthropogenic activities in the Poyang Lake basin. This is consistent with previous studies showing how anthropogenic activities [31], such as hydro-engineering works [44], shipping, mining, and agriculture, affect metal concentrations in Poyang Lake.…”
Section: Concentrations and Spatial Variability Of Tl And Co In The Ssupporting
confidence: 93%
“…However, few studies have been reported on trace metals in lake sediments based on GBCs. Previous research into the evaluation of metals in sediments has generally used background values (BVs) of trace metals as a reference [22,31]. Numerous sediment evaluation methods have been developed, including the geo-accumulation index (I geo ), the single pollution indices (PI), and the potential ecological risk parameter (E r ); using BVs as a basis, all have been widely applied to assess metal concentration in the sediments of Poyang Lake [25,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of total organic carbon (TOC), total nitrogen (TN) and total phosphorus (TP) reflect the nutrient excess of sediments and cause reservoir eutrophication. Zn, Pb, Cd, Cu, Cr, Ni, As and Hg are the eight heavy metals with the greatest ecological risk, so are important indicators for both water environmental monitoring and potential hazard assessment [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Main sources of heavy metal of lake environment are divided into human activities and natural sources [3][4]. In recent years, with rapid development of urbanization and industrialization, artificial sources, such as wastewater discharge, mining and fossil fuel combustion etc., and natural sources, such as geological structure activity, erosion and weathering etc., have caused entry of a great deal of heavy metal pollutants into waters, and made them gathered at lake sediments, which causes huge damage to urban lakes and threatens urban resident health [5][6][7][8]. As important constituent part of urban ecological system, urban lakes play an irreplaceable role in many respects [9].…”
Section: Introductionmentioning
confidence: 99%